Charakteristika umrtnostnich pomeru Romske populace v CSSR - Kalibova, K (Demografie, 1989)
Mortality trends among the Gypsy population of Czechoslovakia are analyzed. Data are from the 1970 and 1980 censuses. The results suggest that the life expectancy among the Gypsy population is as low as 55.3 years for males and 59.9 years for females. Particularly high mortality between the ages of 6 and 35 is noted. (SUMMARY IN ENG AND RUS)
Keywords: Developed Countries; Demography; Europe, Eastern; Sex Factors; vyspělé země; mortalita; Length Of Life; východní Evropa; populace; populační charakteristiky; Population Dynamics; Population Characteristics; naděje dožití; Longevity; Ethnicity; Population; Europe; Mortality; Ethnic Groups; Eastern Europe; sexuální faktory; populační dynamika; kultura; Československo; Demographic Factors; dlouhověkost; Czechoslovakia; demografie; etnicita; Cultural Background; Differential Mortality; Life Expectancy; Culture; Evropa